(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Physical characteristics that determine the individuality of a person plays a pivotal role in medicolegal investigation. Stature is one of such characteristics which serves as an identification data both in living & dead. In this study 200 medical students (100 males & 100 females) between the age group of 18-22yrs participated in finding the correlation between the stature & measured variables of an upper limb i.e., length & breadth of both hands, length of both middle finger, length of bilateral forearm & length of bilateral arm. The F-ratio in the ANOVA test depicts that the regression coefficient are statistically significant in predicting the stature in females (F (10,89) = 16.073, p<0.0005), males (F (10,89) = 26.601, p<0.005) & pooled sample including both male & female (F (10,189)= 92.211, p<0.005). Furthermore, the coefficient of determination (R2) is 0.644 in females, 0.749 in males & 0.830 in pooled sample. The regression equation was also derived using S.P.S.S (I.B.M version 20, Armonk, NY, U.S.A).